2018
DOI: 10.1007/s11325-018-1635-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio decreases in obstructive sleep apnea treated with mandibular advancement devices

Abstract: The neutrophil-to-lymphocyte ratio may be useful in documenting improvement in inflammation for OSA patients treated with mandibular advancement devices. Our results specifically suggest that the NLR values are associated with the decrease in the ODI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Four previous reports found mild, but statistically significant correlations between NLR and AHI [ 54 , 79 , 81 , 85 ], and several prospective studies documented a decrease in NLR after OSA treatment (1 month with a mandibular advancement device [ 86 ], 3 months of CPAP [ 81 , 87 ]). On the contrary, Ozdemir et al [ 62 ], failed to document a significant impact of CPAP on NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous reports found mild, but statistically significant correlations between NLR and AHI [ 54 , 79 , 81 , 85 ], and several prospective studies documented a decrease in NLR after OSA treatment (1 month with a mandibular advancement device [ 86 ], 3 months of CPAP [ 81 , 87 ]). On the contrary, Ozdemir et al [ 62 ], failed to document a significant impact of CPAP on NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Halawani compared the NLR value in OSA patients before and after treatment with mandibular advancement devices. They found that NLR was higher in those with moderate to severe OSA than in those with mild OSA, and in the following subgroup analysis, there was a synchronously significant decline in the NLR and AHI in the group with optimal treatment [ 40 ]. There is a paucity of data on the predictive significance of NLR in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory biomarkers. Al-Halawani et al [70] reported a significant change in the neutrophil-lymphocyte ratio, a hematologic index of systemic inflammation, after 3-months of MAD treatment. In subgroup analysis, only the optimally treated group showed a significant decrease.…”
Section: N-terminal Pro-brain-type Natriuretic Peptide (Nt-pro-bnp)mentioning
confidence: 99%